2018
DOI: 10.1093/mnras/sty3390
|View full text |Cite
|
Sign up to set email alerts
|

The UTMOST pulsar timing programme I: Overview and first results

Abstract: We present an overview and the first results from a large-scale pulsar timing programme that is part of the UTMOST project at the refurbished Molonglo Observatory Synthesis Radio Telescope (MOST) near Canberra, Australia. We currently observe more than 400 mainly bright southern radio pulsars with up to daily cadences. For 205 (8 in binaries, 4 millisecond pulsars) we publish updated timing models, together with their flux densities, flux density variability, and pulse widths at 843 MHz, derived from observati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 111 publications
1
57
0
Order By: Relevance
“…While we used the proper motion of PSR B1706-16 from Fomalont et al (1997) ζ Oph B1706−16 UCL 2nd derivative of the frequency, 0.9 ± 0.2 · 10 −24 s −3 , e.g. due to glitches (Jankowski et al 2019 Zou et al (2005) show (their figure 2) that in particular the right ascension and, hence, proper motion in declination have strong uncertainties for such short epoch differences. We therefore consider the Fomalont et al (1997) proper motion the most reliable.…”
Section: The New Case: ζ Oph and Psr B1706-16mentioning
confidence: 99%
“…While we used the proper motion of PSR B1706-16 from Fomalont et al (1997) ζ Oph B1706−16 UCL 2nd derivative of the frequency, 0.9 ± 0.2 · 10 −24 s −3 , e.g. due to glitches (Jankowski et al 2019 Zou et al (2005) show (their figure 2) that in particular the right ascension and, hence, proper motion in declination have strong uncertainties for such short epoch differences. We therefore consider the Fomalont et al (1997) proper motion the most reliable.…”
Section: The New Case: ζ Oph and Psr B1706-16mentioning
confidence: 99%
“…Large-scale, multi-object radio timing campaigns devoted to systematic searches for pulsar glitches are currently carried out at the Jodrell Bank (Espinoza et al 2011) and Parkes (Yu et al 2013;Yu & Liu 2017) Observatories. These campaigns are supplemented by additional current programs such as CHIME (Ng 2018) and UTMOST (Jankowski et al 2019) that take place at the Dominion Radio Astrophysical Observatory and Molonglo Synthesis Telescope respectively. The analysis in this paper combines the above observations with historical data sets from the Hartebeesthoek Radio Astronomy Observatory (Buchner & Flanagan 2008), Mount Pleasant Radio Observatory (Palfreyman et al 2016), Arecibo Observatory (Arzoumanian et al 2018), and Jet Propulsion Laboratory (Downs 1981).…”
Section: Datamentioning
confidence: 99%
“…ishnan et al 2020). As part of the timing programme, updated rotational models for 205 pulsars were published in the first paper of this series (Jankowski et al 2019) and 9 pulsar glitches have been reported so far (Jankowski et al 2015a(Jankowski et al ,b, 2016(Jankowski et al , 2017Lower et al 2018Lower et al , 2019.…”
Section: Introductionmentioning
confidence: 99%